2016
DOI: 10.1016/j.otsr.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-finger flap for reconstruction of fingertip amputations: Long-term results

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 13 publications
0
28
0
2
Order By: Relevance
“…advancement flap [6,7&8] and cross-finger flap [9,10,11,12,13,14,15,16,17] and homodigital neurovascular flap. [18] In consultation with patient, every surgeon must choose the type of coverage that appears to be most appropriate for that individual's need.…”
mentioning
confidence: 99%
“…advancement flap [6,7&8] and cross-finger flap [9,10,11,12,13,14,15,16,17] and homodigital neurovascular flap. [18] In consultation with patient, every surgeon must choose the type of coverage that appears to be most appropriate for that individual's need.…”
mentioning
confidence: 99%
“…Rabarin et al reported a long-term follow-up of 19.7 years with no pain at the donor site, especially in the fingertip, and no neuralgia, necrosis, or wound abnormality. 21 These results can be further supported in applying the current methods to patients.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, long-term follow-up of cross-finger flap technique reported very good sensory recovery. 21,22 When two-point discrimination results were compared between the innervated flap and the reverse island flap, the neurovascular island flap was superior at the initial stage, but there was no difference at the end of follow-up. Rabarin et al reported a long-term follow-up of 19.7 years with no pain at the donor site, especially in the fingertip, and no neuralgia, necrosis, or wound abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Zu beachten ist, dass der DMCA-4-Lappen nur in 80 % aller Fälle vorliegt, sodass der DMCA-Lappen keine sichere Option bei Kleinfingerdefekten darstellt [10]. Diese Lappentechnik eignet sich bei palmaren Defektwunden an den Mittel-oder Grundgliedern [2,9]. Als adipofaszialer "reversed" Cross-Finger-Lappen kann er auch bei dorsalen Defekten eingesetzt werden, wobei dann der Hebedefekt mit einem Hauttransplantat versorgt werden muss [8].…”
Section: Dmca-lappenunclassified